How Does GDPR Support Healthcare Transformation to 5P Medicine? - Blobel, Bernd; Ruotsalainen, Pekka (Studies in health technology and informatics, 2019)
Health systems advance towards personalized, preventive, predictive, participative precision (5P) medicine, considering the individual's health status, contexts and conditions. This results in fully distributed, highly dynamic, highly complex business systems and processes with multiple, comprehensively cooperating actors from different specialty and policy domains, using their specific methodologies, terminologies, ontologies, knowledge and skills. Rules and regulations governing the business process as well as the organizational, legal and individual conditions, thereby controlling the behavior of the system, are called policies. Trust and confidence needed for running such system are strongly impacted by security and privacy concerns controlled by corresponding policies. The most comprehensive policy dealing with security and privacy requirements and principles in any business collecting, processing and sharing personal identifiable information (PII) is the recently implemented European General Data Protection Regulation (GDPR). This paper investigates how GDPR supports healthcare transformation and how this can be implemented based on international standards and specifications.
Keywords: zabezpečení počítačových systémů; Privacy; European data protection; soukromí; governing; Computer Security; osobní údaje; privacy; Delivery of Health Care; Personally Identifiable Information; lékařství; poskytování zdravotní péče; Medicine